Pitfall or priority drift? Participatory tree domestication programs: The case of agroforestry in the Peruvian Amazon. (2nd October 2016) - Wiersberg, Thorsten; Callo-Concha, Daniel; Ewert, Frank
ABSTRACT: The Agroforestry Tree Domestication Program was globally launched in the 1990s by the World Agroforestry Center to increase farmers' living standards and slow deforestation. After 20 yr of operation, we screen the impacts on farmers' livelihoods and prospects in one of the implementation sites: the Ucayali region of the Peruvian Amazon. We contrast the viewpoints of two sets of stakeholders: (a) "outsiders"—scientists, technicians, and development workers; and (2) "insiders"—local farmers organized and not organized. Group and semistructured interviews were used for data collection, and system analyses were conducted for their integration and interpretation. Results diverge by subset. "Outsiders" praised the program lastingness but questioned its dependence on external parties for management; they considered land property and product marketing keys to persist and succeed. In contrast, "insiders" considered the program financially not viable as well as third-party and locally dependent. As an alternative they had initiated activities, both forestry related and otherwise, to profit from their acquired technical and managerial skills. Based on these findings, broadening stakeholders' diversity and set conveniently roles and decision power during the rationale and implementation phases of similar initiatives could prevent such divergences.